Male and female students' uptake in responding to oral corrective feedback - Zaky Dzulhiza Hawin Amalia; Endang Fauziati; Sri Marmanto (Journal on English as a Foreign Language, 2019)
This study aims at investigating male and female students’ ‘uptake’ to the lecturer’s oral corrective feedback (OCF). This study used a qualitative method using a case study design. Thirty-nine students in the English Education Department participated in this study. They consisted of eleven male students and twenty-eight female students. All participants in this study were taking Survival Speaking class. The data were collected through observation of six hours of speaking classroom interaction. It was then analyzed through three stages: data condensation, data displays and drawing conclusion, and verification. The findings revealed that explicit correction is the most widely used and leads to the most amount of repair. The data obtained from the male students show that explicit correction leads to uptake with repair, whereas the four implicit feedback strategies i.e. clarification request, metalinguistic feedback, elicitation, and repetition mostly lead to uptake with need-repair. Furthermore, the data obtained from the female students show that explicit correction, recast, and metalinguistic feedback mostly lead to uptake with repair, whereas clarification request, elicitation, and repetition mostly lead to uptake with need-repair. Hence, the results of this study will show us which type of oral corrective feedback induces successful feedback and uptake.